COMPUTED TOMOGRAPHY OF BRAIN IN EPILEPTIC PATIENTS - SINTHUNYATHUM, Supang; CHIEWVIT, Pipat (The ASEAN Journal of Radiology, 2023)
Objective: Toassess the yields of imaging findings of computed tomography (CT) of the brain and to detect CT findings in epileptic patients. Materials and Methods: Study in 63 epileptic patients admitted in Phrachomklao Hospital, Phetchaburi, Thailand during January 2004-June 2007. CT scan with intravenous contrast administration was performed in all patients. The radiologic findings were assessed by one radiologist . Results: 63 epileptic patients with an average age of 37 years (range 1-92 yrs). 35 were males, and 28 females. They were stratified into three age groups, including young age (1-30 years old), middle age (31-50 years old) and elderly (over 50 years old ). Most common CT finding in all aging groups were idiopathic (non-related finding or normal finding), found in young age group = 64%, middle age group = 62.5% and elderly group = 50%; Total cases with idiopathic findings = 38/63 = 60.31%. The causes of epilepsy could be identified in 25 cases, 39.69% in this report. The causes could be identified easier and better in the elderly group in comparison with in the young and middle age groups. The result of this study was compared with the result of MRI in epileptic adult patients: experience in Ramathibodi Hospital.1 Conclusion: CT is important in the diagnosis of epilepsy and assessment of the disease, which may be treatable but it is not standard investigation for epileptic patients in comparison with EEG and MRI. The yield of CT is for detecting the cause in some patients such as stroke in elderly patients, vascular abnormality in young adult (AVM), cerebral infection, brain tumor and some congenital lesions.